Understanding Predictors That Influences Relationship Marketing in Unit Trust Industry - Pathmananathan, P. Ravindran; Aseh, Khairi (Archives of Business Research, 2021)
Relationship marketing has been recognised as an excellent way to build an exclusive long-term relationship with their clients in today's dynamic global marketplace. Personal connection is becoming increasingly important to a growing number of businesses. A unit trust is an unincorporated common store structure that enables assets to hold resources and give benefits that go directly to singular unit proprietors as opposed to reinvesting them once again into the reserve.The aim of this research is to emphasise the significance of personal connection and unit trust in the service industry. This research was conducted using a questionnaire that was distributed to 200 customers of unit trust agents in Penang. It can be concluded that relationship marketing is essentially corresponded with personal connection and consumer loyalty as well as client retention.